Genetic parameters for calving rate and age at first calving in Hereford heifers - Callis, Brandon LaKeith (Kansas State University, 2010)
The purpose of this study was to estimate the heritability of calving rate and age at first calving in Hereford heifers, and evaluate whether age at calving would add accuracy to a genetic evaluation of calving rate. Pedigree and performance data on Hereford heifers born between 2001 and 2007 was provided by the American Hereford Association. After editing to exclude animals that did not fit inclusion criteria, the evaluated dataset contained 94,709 heifers with calving status information. Data were analyzed using single and two-trait animal models to obtain heritability estimates, and genetic correlation between calving rate and age at first calving was determined using MTDFREML. Contemporary groups for calving traits were defined as heifers that were in the same yearling weight contemporary group, and remained in the ownership of the same breeder through the age that they would be expected to calve. Estimates of heritability for calving rate and age at first calving from single-trait models were 0.25, and 0.12, respectively. Genetic correlation between calving rate and age at first calving was -0.01. Calving rate is moderately heritable in Hereford heifers, and can be used in genetic evaluation of sires to improve the trait through selection. Age at first calving has minimal genetic relationship to calving rate, and is not useful in increasing accuracy of selection for calving rate.
Keywords: heifers; age at first calving; calving rate; Agriculture, Animal Culture and Nutrition (0475)